A Survey on Patient Safety Using the Farsi Version of the Safety Attitudes Questionnaire in Iran - Sogand Tourani; Rahim Khodayari Zarnaq; Jalal Arabloo; Anvar Esmaili; Sanaz Taghizadeh; Omid Khosravizadeh (Tehran University of Medical Sciences, 2016)
Background and Aim: Patient safety is a critical element of health care quality, and is a priority of health system that pursue to improve the quality of health services. This study aims to determine the attitude the nurses about patient safety in hospitals of Tehran University of Medical Sciences. Materials and Methods: Nurses employed in 7 emergency and intensive care ward specialty and subspecialty hospital affiliated with Tehran University of Medical Sciences was invited to anonymously complete safety attitudes survey. Reliability of the questionnaires was evaluated by calculating Chronbach's alpha. ANOVA were used to compare the score means between the wards. Spearman correlation test was used to analyze the correlation between the safety dimensions and the outcome variables. Results: The results showed that the highest score was dedicated to stress recognition, and the lowest score was related to management perception and working conditions. No significant difference was between the perceptions of emergency department nurses and intensive care nurses with various aspects of safety culture in hospitals. Conclusion: Patient safety status described as acceptable in emergency and intensive care wards. There is a need to understanding of the atmosphere and the culture of safety by hospital executives deeply.